The development of direct 3-dimensional printing of patient-specific mitral valve in soft material for simulation and procedural planningCentral MessagePerspective - Shokoufeh Cheheili Sobbi, MD; Milou Pauli, BSc; Marvin Fillet, BSc; Jos G. Maessen, MD, PhD; Peyman Sardari Nia, MD, PhD (JTCVS Techniques)
Objectives: Replicating 3-dimensional prints of patient-specific mitral valves in soft materials is a cumbersome and time-consuming process. The aim of this study was to develop a method for a direct 3-dimensional printing of patient-specific mitral valves in soft material for simulation-based training and procedural planning. Methods: A process was developed based on data acquisition using 3-dimensional transesophageal echocardiography Cartesian Digital Imaging and Communication of Medicine format, image processing using software (Vesalius3D, Blender, Meshlab, Atum3D Operation Station), and 3-dimensional printing using digital light processing, an additive manufacturing process based on photopolymer resins. Experiments involved adjustment of 3 variables: curing times, model thinness, and lattice structuring during the printing process. Printed models were evaluated for suitability in physical simulation by an experienced mitral valve surgeon. Results: Direct 3-dimensional printing of a patient's mitral valve in soft material was completed within a range of 1.5 to 4.5 hours. Prints with postcuring times of 5, 7, 10, and 15 minutes resulted in increased stiffness. The mitral valves with 2.0-mm and 2.4-mm thinner leaflets felt more flexible without tear of the sutures through the material. The addition of lattice structures made the prints more compliant and better supported suturing. Conclusions: Direct 3-dimensional printing of a realistic and flexible patient-specific mitral valve was achieved within a few hours. A combination of thinner leaflets, reduced curing time, and lattice structures enabled the creation of a realistic patient-specific mitral valve in soft material for physical simulation.